A 3D-printed ultra-high Se loading cathode for high energy density quasi-solid-state Li–Se batteries. Issue 1 (5th December 2019) - Gao, Xuejie; Yang, Xiaofei; Wang, Sizhe; Sun, Qian; Zhao, Changtai; Li, Xiaona; Liang, Jianwen; Zheng, Matthew; Zhao, Yang; Wang, Jiwei; Li, Minsi; Li, Ruing; et al.
Abstract : A quasi-solid-state Li–Se battery assembled with an ultra-high Se loading of 20 mg cm −2 delivers the highest reported areal capacity of 12.99 mA h cm −2 at 3 mA cm −2 . Abstract : Quasi-solid-state lithium–selenium batteries (QSSLSEBs) assembled with gel polymer electrolytes (GPEs) are a promising class of next-generation rechargeable batteries due to their safety, high energy density and shuttle-free charging/discharging process. Nevertheless, both poor Li + transport in thick electrodes and Li dendrite growth limit the improvements of the current density as well as Se loading, resulting in low energy/power densities. Herein, we proposed to combine a 3D-printed carbon nanotube (CNT) interlayer to protect the Li anode with a 3D-printed Se cathode (named 3DPSe) filled with GPEs in high Se loading cathodes to achieve ultra-high energy/power-density QSSLSEBs. Benefitting from the 3D-printed CNT interlayer in suppressing Li dendrite growth, the Li–Li symmetric cell stably runs for 400 h (3 mA cm −2 ; 3 mA h cm −2 ), which is almost one order of magnitude longer than the interlayer-free cell. Moreover, 3DPSe acts as a host for GPE impregnation to fabricate interconnect Li + transport channels in the thick Se cathode, enabling fast Li + transport. Accordingly, the QSSLSEB assembled with an ultra-high Se loading of 20 mg cm −2 delivers the highest reported areal capacity of 12.99 mA h cm −2 at 3 mA cm −2 . This work is expected to open up promising opportunities to develop other high-energy/power-density solid-state lithium batteries (SSLBs).